Analisis Tindak Tutur Representatif Ketiga Ahli Hukum Tata Negara Sebagai Bintang Film Dokumenter Dirty Vote - Alyanisa Lintang Sekar Langit; Dhewi Safitri; Zulia Munna Khasanah; Sindi Awaliyah; Asep Purwo Yudi Utomo; Riyadi Widhiyanto; Rossi Galih Kesuma (STIKes Ibnu Sina Ajibarang, 2024)
YouTube has become an alternative medium for showcasing videos of varying lengths. Dirty Vote is one such long-form video, presented as a documentary film, available on YouTube. This documentary film is performed by three state law experts who also play the roles of researchers analyzing the content featured in the film. Starring Zainal Arifin Mochtar, Bivitri Susanti, and Feri Amsari, the film discusses political corruption that has occurred in Indonesia over the past few years. This research aims to analyze the speech acts performed by the three main stars of the documentary film